Wpływ systemu wyborczego mieszanego na system polityczny Nowej Zelandii - Szabaciuk, Wojciech (Polityka i Społeczeństwo, 2021)
This article is an attempt to analyze the New Zealand voting system after almost twenty years of experience of working the new system. New Zealand until 1993 was a model of Westminster Democracy with a two-party system and plurality voting system. As a consequence of a referendum in 1993 the voting system of New Zealand was trans-formed from first-past-post to mixed member proportional representation. This change was a cause of the increase in the effective number of parties and political polarization and also was a decreased of the disproportionality of elections. In this paper I want to show the political consequences of Mixed Member Proportional Representation for the party system and the creation of a cabinet for New Zealand. Two major parties after the transition to the new system were no longer able to create a single-party majority cabinet and were forced to begin new relations with small parties. In this work a method of system analyses was used. In conclusions I show that New Zealand has one of the most proportional systems and, despite MMP, New Zealand still has a two-party system.